1989
DOI: 10.1007/bf00439443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulpiride and chlorpromazine on regional cerebral glucose metabolism in schizophrenic patients as determined by positron emission tomography

Abstract: Positron emission tomography (PET) was used to determine regional brain glucose metabolism in schizophrenic patients (n = 17) before and during neuroleptic treatment. The patients had not been treated with neuroleptics for at least 3 weeks before the first study. All suffered from acute psychotic symptoms and were hospitalized to obtain neuroleptic treatment. After determination of regional brain metabolism without neuroleptic treatment, 11 patients were treated with sulpiride (800 mg/day) and 6 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 32 publications
2
14
1
Order By: Relevance
“…Earlier studies using human microsomes showed that numerous brain tissues actively metabolize psychoactive drug substrates including chlorpromazine, imipramine and fluoxetine (Bhagwat et al 1996; Bhamre et al 1995). In addition, several positron emission tomography studies have demonstrated significant differences in glucose metabolism in the lentiform nucleus in patient-versus-control comparisons of psychoactive drugs like fluoxetine and chlorpromazine (Chen et al 2009; Mayberg et al 2000; Wik et al 1989). Each of these studies lends credibility to the findings in this study and future endeavors to further understand the mechanisms by which gene variants in the FMO gene cluster may influence lentiform nucleus volume.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies using human microsomes showed that numerous brain tissues actively metabolize psychoactive drug substrates including chlorpromazine, imipramine and fluoxetine (Bhagwat et al 1996; Bhamre et al 1995). In addition, several positron emission tomography studies have demonstrated significant differences in glucose metabolism in the lentiform nucleus in patient-versus-control comparisons of psychoactive drugs like fluoxetine and chlorpromazine (Chen et al 2009; Mayberg et al 2000; Wik et al 1989). Each of these studies lends credibility to the findings in this study and future endeavors to further understand the mechanisms by which gene variants in the FMO gene cluster may influence lentiform nucleus volume.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with schizophrenia, most (Szechtman et al 1988;Wik et al 1989;Bartlett et al 1991;Buchsbaum et al 1992b;Holcomb et al 1996;Wolkin et al 1996), but not all (Volkow et al 1986;Resnick et al 1988;Cleghorn et al 1991;Buchsbaum et al 1992a), studies also show changes in thalamic activity in response to antipsychotic drugs, as measured by glucose uptake and positron emission tomography (PET). However, in these studies, patients received various drugs and were studied after various lengths of time, from 1 day to 7 years, of treatment, so that the consistent and shared e¤ects of drugs are di¦cult to determine.…”
Section: Introductionmentioning
confidence: 92%
“…With the recent advent of neuroimaging techniques, changes in brain metabolism, reflecting changes in neuronal activity after drug administration, can be visualized at increasingly higher resolution, thus providing a valuable insight into the drug effects on brain function. Studies of exposure to other dopamine D 2 receptor antagonists in psychiatric patients and healthy subjects have revealed areas of increased activity mainly in the basal ganglia and decreased cortical activity, although the sites of cortical decrease varied among studies and drugs (Wik et al ., 1989; Holcomb et al ., 1996; Lahti et al ., 2003; 2005). However, to the best of our knowledge, the effects of metoclopramide on brain metabolism have not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the acute administration of metoclopramide induced bilateral CBF increases in the putamen, lateral globus pallidus and thalamus. The CBF increases in the putamen are consistent with the reported increased metabolism in the dorsolateral striatum following administration of other first‐generation antipsychotics, both in control subjects (Bartlett et al ., 1994) and psychiatric patients (Wik et al ., 1989; Lahti et al ., 2003; 2005), measured using PET with fluorodeoxyglucose or 15 O water. The dorsolateral striatum, comprising the dorsolateral regions of the caudate nucleus and most of the putamen, is the brain area richest in dopamine D 2 receptors, and also the area first and most affected by the dopaminergic deficit produced in Parkinson's disease (PD) (Gibb and Lees, 1991).…”
mentioning
confidence: 99%